Kompor Gas Berbahan Bakar Biomassa - Fajri Vidian (Jurnal Rekayasa Mesin, 2009)
The rule of goverment for converting kerosene to gas made problem in rural to get gas. At this study have conducted modeling, manufacturing and testing a biomass gasification stove. The stove have 74.5 cm total height, 42 cm burner height, 16.5 cm diameter dan ash hopper . The results of eksperiment using rubber wood and cob as fuel showed stove could produce flame 30 until 40 minute with 4 until 6 for one bed fuel, the time for boiling water are 4 until 6 minute.